Strategi Pembelajaran Ekstrakulikuler Tahfidz Al-Qur’an Terhadap Pencapaian Hapalan Siswa di UPTD SMPN 3 Kec. Harau - Fatmi S, Fitri J; Dewi, Puti Andam; F, Farnice (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was motivated by several problems arising from the inaccurate achievement of memorizing the Al-Qur’an Tahfiz Extracurricular at UPTD SMPN 3 HARAU, some of which were students not achieving the daily target in memorizing the verses of the Al-Qur’an, students having difficulty in repeating memorized Al-Qur’an. One solution is to 1) bring in competent tahfiz teachers 2) The school collaborates with the Tahfiz cottage 3) Carry out rote literacy in the prayer room 4) Set a target for achieving at least one verse a day. This has an impact on achieving the target of memorizing the Al-Qur’an for students at UPTD SMPN 3 HARAU. The aim of writing this article is to describe the strategy for achieving memorization of the Al-Qur’an extracurricular Tahfiz curricular at UPTD SMPN 3 HARAU. This research uses a type of field research with descriptive qualitative research by describing the actual situation in the field. The results of the research concluded that by implementing the learning strategies that have been explained in this article, UPTD SMPN 3 HARAU students were able to achieve the memorization target every day in accordance with what had been implemented by the extracurricular tahfiz teaching team at UPTD SMPN 3 HARAU.